Competition and Mergers with Strategic Data Intermediaries - David Bounie; Antoine Dubus; Patrick Waelbroeck (Center for Economic Studies and ifo Institute (CESifo), 2021)
We analyze competition between data intermediaries collecting information on consumers, which they sell to firms for price discrimination purposes. We show that competition between data intermediaries benefits consumers by increasing competition between firms, and by reducing the amount of consumer data collected. We argue that merger policy guidelines should investigate the effect of the data strategies of large intermediaries on competition and consumer surplus in related markets.
Keywords: L13; L40; L86; 330; data; mergers; competition; consumer surplus